Endocrine aspects of male sexual dysfunctions - Buvat, J.; Maggi, M.; Gooren, L.; Guay, A.T.; Kaufman, J.; Morgentaler, A.; Schulman, C.; Tan, H.M.; Torres, L.O.; Yassin, A.; Zitzmann, M. (2010)
Introduction. Endocrine disorders may adversely affect men's sexual function. Aim. To provide recommendations based on best evidence for diagnosis and treatment of endocrine-related male sexual dysfunctions. Methods. The Endocrine Aspects of Male Sexual Dysfunctions Committee, including 11 members from eight countries and four continents, collaborated with the Endocrine subcommittee of the Standards Committee of the International Society for Sexual Medicine. Medical literature was reviewed in detail, followed by extensive internal committee discussion over 2 years, then public presentation and discussion with the other experts before finalizing the report. Main Outcome Measure. Recommendations based on grading of evidence-base medical literature and interactive discussion. Results. From animal studies, it is derived that testosterone modulates mechanisms involved in erectile machinery, including expression of enzymes that both initiate and terminate erection. In addition, testosterone is essential for sexual motivation. Whether these findings could be extrapolated to human erections is unclear. Testosterone plays a broad role in men's overall health. Recent studies have established strong associations between low testosterone and metabolic and cardiovascular imbalances. In some studies, low testosterone decreased longevity; however, longitudinal studies do not support the predictive value of low testosterone for further cardiovascular events. The article proposes a standardized process for diagnosis and treatment of endocrine-related male sexual dysfunctions, updating the knowledge on testosterone and prostate safety. There is no compelling evidence that testosterone treatment causes prostate cancer or its progression in men without severe testosterone deficiency (TD). The possible roles of prolactin and thyroid hormones are also examined. Conclusions. Men with erectile dysfunction, hypoactive sexual desire and retarded ejaculation, as well as those with visceral obesity and metabolic diseases, should be screened for TD and treated. Prospective interventional studies are required before screening for TD in more conditions, including cardiovascular diseases, and considering correction as preventive medicine as much data suggests. Buvat J, Maggi M, Gooren L, Guay AT, Kaufman J, Morgentaler A, Schulman C, Tan HM, Torres LO, Yassin A, and Zitzmann M. Endocrine aspects of male sexual dysfunctions. J Sex Med 2010;7:1627-1656.